2019
DOI: 10.2174/1389450119666180924145156
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Rifaximin in Prophylaxis of Spontaneous Bacterial Peritonitis: A Systematic Review and Meta-analysis

Abstract: Aim: The role of rifaximin in the prevention of Spontaneous Bacterial Peritonitis (SBP) is not well studied. The aim of this meta-analysis was to evaluate the role of rifaximin in the prevention of SBP. Methods: A computerized literature search for relevant clinical trials was conducted during August 2017. Data on Frequency of SBP, the success rate of prevention of SBP, mortality rate, hepatorenal syndrome, septic shock, hepatic encephalopathy, and GIT bleeding were extracted and pooled as Risk Ratio (RR) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…As for ascetic fluid-total protein levels, this is consistent with Nabiel et al, [8] and Paul et al [10] who have reported that ascitic fluid opsonic activity closely correlates with fluid protein concentration; fluids < 1.0 g/dl of protein have reported decreasing opsonic activity and thus highly susceptible to protein concentrations With respect to the amount of ascetic fluid albumin in SBP patients, this was agreed with Paul et al [10], which may be explained by the decreased functional activity of hepatocytes and innate immune system fatigue creating what was referred to as immune dysfunction related cirrhosis [11].…”
Section: Discussionsupporting
confidence: 81%
“…As for ascetic fluid-total protein levels, this is consistent with Nabiel et al, [8] and Paul et al [10] who have reported that ascitic fluid opsonic activity closely correlates with fluid protein concentration; fluids < 1.0 g/dl of protein have reported decreasing opsonic activity and thus highly susceptible to protein concentrations With respect to the amount of ascetic fluid albumin in SBP patients, this was agreed with Paul et al [10], which may be explained by the decreased functional activity of hepatocytes and innate immune system fatigue creating what was referred to as immune dysfunction related cirrhosis [11].…”
Section: Discussionsupporting
confidence: 81%
“…The procalcitonin level was significantly correlated with the (ascitic fluid) white blood cell count (rs=0.404, P<0.01) [20,37]. Cekin et al, reported higher procalcitonin serum levels in patients with positive bacterial culture in ascitic fluid compared to patients without culture positivity [21,38]. Finally, Abdel-Razik et al, demonstrated that at a cutoff value of 0.94 ng/mL, serum procalcitonin had 94.3% sensitivity and 91.8% specificity for detecting spontaneous bacterial peritonitis [39].…”
Section: Discussionmentioning
confidence: 99%
“…In the inflammatory process, the synthesis of SAA is expected. Certainly, activated monocytes express and release SAA [ 30 , 31 ]. In spite of local SAA release, there is a serum contribution of SAA in the effusion due to a positive strong correlation between them [ 30 - 32 ].…”
Section: Discussionmentioning
confidence: 99%